Sorry John–try again next year. Issue 6138 (2nd September 1978) - Rowlands, B J
Abstract : The new legislation affecting foreign medical graduates has placed several obstacles in the path of potential visitors and immigrants to the United States. Now that there is no longer a shortage of doctors in the USA the need for these new laws is clear, but their implementation has been hasty and has allowed no time for planned transition. If further modifications are made, which may well happen, every effort should be made to disseminate information about new requirements as widely and rapidly as possible.